2017
DOI: 10.1016/j.jtho.2016.09.134
|View full text |Cite
|
Sign up to set email alerts
|

Heart Dose Is an Independent Dosimetric Predictor of Overall Survival in Locally Advanced Non–Small Cell Lung Cancer

Abstract: Introduction: In the randomized trial of standard-versus high-dose chemoradiotherapy for locally advanced (LA) NSCLC (Radiation Therapy Oncology Group 0617), overall survival (OS) was worse in the high-dose arm. Although heart dose was suggested as a contributing factor, actionable parameters have not been established. We present an analysis of clinical and dosimetric parameters affecting OS in this patient population, focusing on heart dose. Methods: Clinical data were collected on 416 patients with LA NSCLC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
188
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(196 citation statements)
references
References 21 publications
3
188
1
4
Order By: Relevance
“…It is especially important for patients with upper gastrointestinal tumors, given its impact on organs in the mediastinum and abdomen. Dose and volume to critical organs, including the heart, lungs, kidneys, liver, small bowel, and spinal cord, have been linked to morbidity, and in some cases survival . The dosimetric superiority of more conformal techniques such as intensity‐modulated RT (IMRT) over 3‐dimensional conformal RT (3DCRT) has been well documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is especially important for patients with upper gastrointestinal tumors, given its impact on organs in the mediastinum and abdomen. Dose and volume to critical organs, including the heart, lungs, kidneys, liver, small bowel, and spinal cord, have been linked to morbidity, and in some cases survival . The dosimetric superiority of more conformal techniques such as intensity‐modulated RT (IMRT) over 3‐dimensional conformal RT (3DCRT) has been well documented.…”
Section: Discussionmentioning
confidence: 99%
“…Dose and volume to critical organs, including the heart, lungs, kidneys, liver, small bowel, and spinal cord, have been linked to morbidity, and in some cases survival. [12][13][14]22 The dosimetric superiority of more conformal techniques such as intensitymodulated RT (IMRT) over 3-dimensional conformal RT (3DCRT) has been well documented. Series have shown significant reductions in doses to the lungs (mean volume of the lung receiving a dose of at least 10 Gy [V10] and V20) and heart (mean, V30 [right coronary]) in patients with esophageal and GEJ adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…5 On the other hand, studies with a larger number of patients including RTOG 0617 and analyses by Stam et al (which analyzed patients with early stage lung cancer) and Speirs et al were able to find an association between heart dose and decreased survival. 4,8,43 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also examined the association between mean heart dose and cardiac events/disease, finding an ∼4-16% increased risk per Gy of mean heart dose (7)(8)(9). Studies have also suggested RIHD can occur in non-small cell lung cancer patients within 2 years post-radiation exposure (8)(9)(10)(11). In a number of lung cancer studies, mortality rates were cardiac dose-dependent, either based on mean heart dose (12) or with the percent of heart receiving 5 Gy (13), 30 Gy (13), or 50 Gy (10).…”
mentioning
confidence: 99%
“…Studies have also suggested RIHD can occur in non-small cell lung cancer patients within 2 years post-radiation exposure (8)(9)(10)(11). In a number of lung cancer studies, mortality rates were cardiac dose-dependent, either based on mean heart dose (12) or with the percent of heart receiving 5 Gy (13), 30 Gy (13), or 50 Gy (10). In pediatric and young adult cancer patients who received cardiac radiation, there is over a 6-fold relative risk of RIHD, defined as congestive heart failure, myocardial infarction, pericardial disease, and/or valvular abnormalities (14).…”
mentioning
confidence: 99%